Menelaah Fenomena Klitih di Yogyakarta Dalam Perspektif Tindakan Sosial dan Perubahan Sosial Max Weber - Putra, Ahmad; Suryadinata, Sartika (Asketik : Jurnal Agama dan Perubahan Sosial, 2020)
This paper explains that the phenomenon of klitih in Yogyakarta is an action that is contrary to existing norms in society. The perpetrators of klitih who incidentally are students, enter into the trap of delinquency that causes victims. Actions that they do actually damage their own personality and unsettle for motorists at night. Besides that, it causes deep sadness that educational institutions have not succeeded in establishing good character for students and adolescents in this country, especially for perpetrators. This research connects the phenomenon of klitih in Yogyakarta with Max Weber's views through his two theories, namely social action and social change. This research is qualitative in nature with its descriptive analysis and through accurate sources. The results of this research are: First, the action of the perpetrators who do a kind of a game and as a form of recognition by their peers: Second, parents, educational institutions and the community are not optimal in providing supervision to adolescents and students, so that many teenagers in this epoch are involved on various delinquents; Third, the target of the clitih action is motorists who pass certain areas at night. Overall the phenomena that occur are consistent with Max Weber's theory that humans have an action done with a sense of emotion, prioritizing their own interests, so they no longer pay attention to existing norms and think irrationally.